Sufficient conditions from countably Lipschitz to be strongly generalized absolutely continuous - Indrati, Christiana Rini (KOMUNITAS Analisis Matematika INDONESIA, 2023)
The CL-integral is an integral that is defined by using countably Lipschitz condition. The CL-integral is more general than the Lebesgue integral, but it is more specific than Denjoy integral in the wide sense. The Denjoy integral in the wide sense is more general than the Henstock-Kurzweil integral. In this paper, it will be given some conditions such that a CL-integrable function is Henctock-Kurzweil-integrable on [a, b].